Telaah Kritis Kurikulum Inklusi dalam Pembelajaran Anak Berkebutuhan Khusus di Madrasah Ibtidaiyah Terpadu: (Critical Review of Inclusive Curriculum in Learning for Children with Special Needs at Integrated Islamic Elementary School) - Rosyidah, Alfi; A. Qomarudin (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2025)
This study aims to critically examine the implementation of an inclusive curriculum in learning for children with special needs at MI Ar-Roihan Lawang. The background of this study is based on the issue of gender equality and the right to education for all Indonesian people. MI Ar-Roihan is interesting because not all schools, especially madrasahs, implement an inclusive system. This study uses a descriptive qualitative method to explore aspects of implementing the inclusive curriculum. The results of the study show: (1) psychological tests were conducted to determine the abilities and obstacles of students; (2) each class has a special learning style, including a special therapy class for children with special needs; and (3) learning objectives for children with special needs are adjusted to certain limits that are different from children in general. This study provides an original contribution in explaining how inclusive madrasahs can be implemented and have a positive impact on society while opening up opportunities for further studies on inclusion in religious-based educational institutions.